Citizen’s Voice on Local Cybermedia Balebengong - Bangun, Cendera Rizky Anugrah (Bina Nusantara University, 2016)
The development of technology has played a big role to citizen journalism. Balebengong is an example of Local cyber citizen journalism media. The purpose of this research was to understand how the practices of the public sphere in the local cyber media Balebengong. The used theories in this research were citizen journalism and the public sphere. With interpretive paradigm and qualitative method, this research used interview and online data. The object of research was local cyber media Balebengong and key informant who were the contributor and editor of Balebengong. The implications of this research were expected to provide inputs for traditional media in providing more public space portion citizen journalism or more so that the public could also participate in the nation. The result of this research is Balebengong has provided enough public spheres for the members of its society to contribute to it.